2022
DOI: 10.25082/amler.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the coding skills of teachers in a low dropout Python MOOC

Abstract: In this paper, we present a structured approach to developing an outreach program aimed at improving the coding abilities of pre- and in-service teachers. The paper presents the design and development decisions made using the ADDIE model. External evaluators assessed the material's quality, confirmed the estimated workload, and examined the material's relevance to the educational goals. Learners’ active participation was encouraged through multiple quizzes, and learners were assisted in their learning activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Python is widely used in education. For example, Lazarinis et al [23] conducted a study aimed at enhancing pre-service and in-service teachers' coding skills, in which teachers learned to code and were required to confront problems in a series of ordered steps that demanded them to analyze and organize data in structures. According to Zourmpakis et al [24] teachers can exert considerable effect on the gamification of science education.…”
Section: 2mentioning
confidence: 99%
“…Python is widely used in education. For example, Lazarinis et al [23] conducted a study aimed at enhancing pre-service and in-service teachers' coding skills, in which teachers learned to code and were required to confront problems in a series of ordered steps that demanded them to analyze and organize data in structures. According to Zourmpakis et al [24] teachers can exert considerable effect on the gamification of science education.…”
Section: 2mentioning
confidence: 99%
“…In addition to numerous reviews there are several empirical studies. So, professional development of teachers in computer technology is also considered with application of empirical approach by Lazarinis et al [19]. Analysing digital activism in students Aguayo et al [20] found out that the students were less concentrated than in the traditional classroom and the teachers had to teach them to process the information.…”
Section: Development Of the Phenomenonmentioning
confidence: 99%
“…Being quite popular, the course on learning Python is being introduced into vocational [9] and higher education. In addition, the Python language can be used to develop the coding skills of teachers [10], and other non-specialists in the IT field.…”
Section: Introductionmentioning
confidence: 99%